2017
DOI: 10.1002/pbc.26477
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric neuroendocrine carcinoid tumors: Management, pathology, and imaging findings in a pediatric referral center

Abstract: Contrary to recent epidemiological investigations in adults, appendiceal carcinoid tumors remain the most common site for pediatric carcinoid tumors. Appendiceal carcinoid tumors exhibited benign clinical courses without recurrence during short-term follow-up. Extra-appendiceal gastrointestinal carcinoid tumors exhibited much more aggressive behavior with greater metastases and recurrence. Bronchial carcinoid tumors demonstrated good clinical response to resection even in cases with mediastinal lymph node invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…Another issue is the high proportion of patients lost to FU or who opted out, as it happened in six patients of our series (23% of the total population). This was often reported in the past, 14,16,27 and in our experience it seems a consequence of parents’ decision to look for a second or third opinion in other centers outside the pediatric network.…”
Section: Discussionsupporting
confidence: 50%
“…Another issue is the high proportion of patients lost to FU or who opted out, as it happened in six patients of our series (23% of the total population). This was often reported in the past, 14,16,27 and in our experience it seems a consequence of parents’ decision to look for a second or third opinion in other centers outside the pediatric network.…”
Section: Discussionsupporting
confidence: 50%
“…Neuroendocrine tumors commonly metastasize [19] and research has demonstrated that Tyro3 may contribute to cancer cell motility [20] . We noted a decrease in Tyro3 expression with increasing doses of crizotinib ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of lymph node resection on overall survival for typical bronchial carcinoid in pediatrics has not been clearly defined; however, multiple series have shown that lymphatic spread occurs in up to 20% of pediatric patients of both histologies. 1,5,9,17 Given this information, we believe that lymph node resection should be performed for all enlarged nodes and lymph node sampling should be considered in other patients.…”
Section: Discussionmentioning
confidence: 99%